Comprehensive sanitary survey evaluation of high risk beaches in northern Wisconsin - Busse, Kimberly (My University, 2014)
In 2008 13% of Great Lakes beaches exceeded health standards; approximately 90% of those exceedances were attributed to unknown pollution sources. In this project, sanitary surveys were conducted at all impaired beaches [CWA, 303(d)] in Northern WI to identify pollution sources and drive mitigation. This project covered the entire Lake Superior and northern Lake Michigan shoreline. One inland beach in northern Wisconsin as also selected to assess the transferability of the Great Lakes Beach sanitary survey tool to inland beaches (located on still or flowing waters). This project clearly addressed the goal of identifying unknown pollution sources by not only investigating sources of contamination at numerous locations around Wisconsin, but also began the process of planning for the mitigation of these microbial contamination sources. In years one and two of this project sanitary surveys (SS) were conducted at all northern Wisconsin beaches listed (and proposed) on the 303d list. Study beaches were located on the northern shore of Lake Michigan and Lake Superior, encompassing both rural and urban settings and various stages within the investigative process (none to fairly extensive monitoring with/without mitigation measures). The US EPA Sanitary Survey tools (routine and annual) were used to conduct site assessments for the purpose of determining probable pollutant sources and suggesting mitigation measures. Data collected as part of the sanitary survey process was entered into and archived within the WI "Beach Health" website such that they were accessible for the construction of predictive models. In year three of the study, a sample plan was developed based on previous years data to target potential pollution source identification. Based on three years of data, statistical analysis was conducted to identify sources at each of the ten beaches selected. Source identification was the first step in the effort to improve water quality at recreational beaches in Wisconsin.
A Thesis Submitted In Partial Fulfillment of the Requirement For the Degree of Master of Science Biology Microbiology
Keywords: Beaches; Escherichia coli; Water quality magement; Bacterial pollution of water; Water pollution